2015
DOI: 10.1016/j.ssresearch.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Relational diversity and neighbourhood cohesion. Unpacking variety, balance and in-group size

Abstract: Ethnic diversity is typically measured by the well-known Hirschman-Herfindahl Index. This paper discusses the merits of an alternative approach, which is in our view better suited to tease out why and how ethnic diversity matters. The approach consists of two elements. First, all existing diversity indices are nonrelational. From the viewpoint of theoretical accounts that attribute negative diversity effects to in-group favoritism and out-group threat, it should however matter whether, given a certain level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…Once one takes into account that whites have higher levels of trust than Latinos and blacks, and that diverse neighborhoods have fewer whites, the supposedly negative effect of ethnic diversity disappears. Similar ethnoracial compositional effects have also been found in Europe [ 15 17 ].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Once one takes into account that whites have higher levels of trust than Latinos and blacks, and that diverse neighborhoods have fewer whites, the supposedly negative effect of ethnic diversity disappears. Similar ethnoracial compositional effects have also been found in Europe [ 15 17 ].…”
Section: Introductionsupporting
confidence: 74%
“…Our results thus suggest that social cohesion in Germany, is related not only to individual and household characteristics, but also to characteristics of the immediate neighborhood (cp. [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
“…One prominent argument in this debate holds that individuals face difficulty in sanctioning antisocial behavior across ethnic lines, leading to lower levels of trust and cooperation in ethnically diverse communities ( 5 8 ). However, to date, evidence for this proposition is drawn mainly from the small-group context ( 6 , 7 ) in which coethnicity overlaps with social networks that help individuals to identify defectors and communicate reputational information ( 5 , 9 , 10 ). By contrast, surprisingly little is known about how ethnicity influences social norm enforcement in anonymous encounters which characterize many interactions in complex Western societies ( 4 , 11 , 12 ).…”
mentioning
confidence: 99%
“…Group identity and sense of belonging have been identified as relevant correlates of well-being (for a review, see Smith & Silva, 2011), and they are more likely to develop in the context of the socialising influences of in-group members. Moreover, in-group members are an important source of social and psychological support, especially among minority groups (Almeida, Molnar, Kawachi, & Subramanian, 2009), and thus an individual surrounded by mostly ethnic outgroup members is likely to feel worse than when surrounded by in-group members (see also Koopmans & Schaeffer, 2015). Research on the determinants of social interaction and social identity shows strong evidence for the principle of homophily, i.e., the preference for affiliation and contact with people who are similar in terms of key characteristics, such as ethnicity.…”
Section: Neighbourhood Disorder Ethnic In-group Share and Minority/ mentioning
confidence: 99%
“…For example, studies of different political participation rates among members of ethnic minorities and the majority population demonstrate that as the concentration of a given ethnic group in a local area increases, its members are more likely to become politically involved (Fieldhouse & Cutts, 2008a, 2008b. Similarly, Koopmans and Schaeffer (2015) showed that the neighbourhood in-group share was positively associated with higher levels of trust, efficacy and overall neighbourhood cohesion. In relation to well-being, however, research has been scarce and with mixed findings.…”
Section: Neighbourhood Disorder Ethnic In-group Share and Minority/ mentioning
confidence: 99%